FACTORS INFLUENCING COMMUNITY'S INTEREST IN BUYING JAMBI BATIK - Effiyaldi . (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2019)
The good support of City of Jambi Government had an impact on the rise of the number of Jambi batik craftsmen. However, this rise does not cause a significant influence on people's interest in buying Jambi batik. This study aims to determine the factors that affect people's interest in buying Jambi batik in the city of Jambi. By using factor analysis, this research found that the factors influencing people's interest in buying Batik Jambi are: comfort ability to wear, variety in design, filler ornaments, always update model, safe to wear, primary / main color, secondary color, main ornament, colors, durability, quality, pattern / motif, having characteristic, and privilege. We recommend that all concerned parties, through the local government to make a new breakthrough in order to increase the interest of Jambi people to Jambi batik.